IPTEKS SISTEM INFORMASI MANAJEMEN KEUANGAN DAERAH PADA UPTD BALAI PELATIHAN KESEHATAN PROVINSI SULAWESI UTARA - Arota, Poppy S.; Daleno, Fransisca G.; Rumbayan, Reklesia B. A.; Kaligis, Virginia P.; Suwetja, I Gede (Universitas Sam Ratulangi, 2018)
Implementation of SIMDA at UPTD Health Training Center of North Sulawesi Province used method applied finance SIMDA2.7.0.12 accrual based at UPTD Health Training Center of North Sulawesi Province was based on the Ordinance Ministry of Home Affairs No. 13 2006 about financial management is started of stages of planning, administration, accounting and reporting. Application techniqueSIMDA2.7.0.12version accrual based : according to the Ordinance Ministry of Home Affairs No. 13 2006 IPTEKS technique who applied on manufacture of SIMDA are covers by Budgeting Planning : RKA, RAPBD and other of DPA. Administration :Letter of Provision of Funds (SPD), Letter of Request Payment (SPP). From implementation of examination result finance at UPTD Health Training Center of North Sulawesi Province is showed : implementation of SIMDA 2.7.0.12accrual based has already done through the products produced, namely budgeting and administration have no constraints, while the obstacles faced in accounting and reporting products in producing Operational Reports (LO) and Budgeting and Administration is carried out according to the Ordinance Ministry of Home Affairs No. 13 2006about financial regional management, while the accounting reporting process is carried out according to the Ordinance Ministry of Home Affairs No. 642013 about the application of accrual based government accounting standards.Keywords: Implementation, finance management, accrual based